Evaluating the environmental and economic impacts of mine void infilling: a case study - Morton, A; Johnston, S; Taniane, L (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
This paper presents a study on the environmental and economic impacts of mine void infilling, focusing on a case study of an operating coal mine in Australia referred to as ‘Mine Site A’. The study was initiated to understand the carbon cost of mine void infilling and its implications for enabling high-value post-mining land use (PMLU) initiatives. The potential for some innovative PMLUs that could provide significant sustainable social, economic and environmental value for mining-impacted regional communities is often limited by the infilling of mining voids. Additionally, the act of void infilling incurs financial costs and contributes to greenhouse gas (GHG) emissions from diesel combustion. Alternative and innovative approaches to PMLUs may create the opportunity to redeploy a significant portion of rehabilitation costs towards investment in alternate repurposing and remining PMLUs while contributing to decarbonisation. The study estimates that the GHG emissions from mine pit infilling at Mine Site A amount to 0.9 kg CO2e per tonne of spoil moved, resulting in approximately 121,000 t of CO2e per year. This is equivalent to the emissions generated by 26,000 passenger vehicles driven for a year. The annual diesel consumption for this specific mine site scenario is estimated to be AUD 83 million. These emissions represent only scope 1 emissions from diesel usage for pit infilling activities and do not consider (a) associated scope 2 and scope 3 emissions of mine pit infilling and (b) GHG emissions associated with implementing an alternate PMLU in place of pit infilling. The study emphasises the need for a pilot sitespecific trial study to improve the accuracy of these estimates and to account for variable factors such as spoil data, haul distances and onsite diesel usage. Overall, this paper provides valuable insights into the carbon emissions and financial costs of mine void infilling and its impact on innovative PMLU options. It emphasises the need for a broader research perspective to inform sustainable mine closure and rehabilitation practices.
Keywords: post-mine land use; mine regeneration; greenhouse gas emissions; mine pit infilling; diesel costs